Rancangan UI/UX Aplikasi Pite Tenun Dengan Edukasi Budaya Menggunakan Metode Design Thinking - Wilitama Tantosa; Lalu A Syamsul Irfan Akbar; Cipta Ramadhani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Woven fabric is an Indonesian cultural wealth that can be found in various regions, one of which is in Sukarara Village, Lombok. Sukarara woven fabric is known as